2020
DOI: 10.3390/nu12051510
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Approaches to Stop Hypertension (DASH) Score and Its Association with Sleep Quality in a National Survey of Middle-Aged and Older Men and Women

Abstract: Complex processes appear to link sleep duration and quality with dietary patterns. Numerous studies show healthful benefits of the Dietary Approaches to Stop Hypertension (DASH) diet, but few have examined its association with sleep duration or quality. The current study tested cross-sectional associations of DASH diet quality score with sleep quality among adults. Analyses of participants were from the 2005–2008 wave of the National Health and Nutrition Examination Surveys (n = 3941 adults ≥30 years of age, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…Similar to our study, Liang et al In a study of 3941 American adults found that following a dash diet could effectively improve sleep quality and sleep duration( 22 ). Also, similar to our study, Mossavar-Rahmani in a study of 2,140 Spanish adults found that increasing the Healthy Eating Index effectively increased sleep duration and sleep efficiency( 23 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to our study, Liang et al In a study of 3941 American adults found that following a dash diet could effectively improve sleep quality and sleep duration( 22 ). Also, similar to our study, Mossavar-Rahmani in a study of 2,140 Spanish adults found that increasing the Healthy Eating Index effectively increased sleep duration and sleep efficiency( 23 ).…”
Section: Discussionsupporting
confidence: 91%
“…Kurotani et al And Cao Y et al Showed that consumption of vegetables, fruits and legumes is associated with better sleep quality( 28 ). Liang et al Also found that reduced consumption of vegetables, nuts, and legumes was associated with reduced sleep duration( 22 ). Other studies also confirm that consumption of fruits and vegetables is directly related to sleep duration and sleep quality( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors may be related to increased risks of EDs, and several are especially prevalent for students in the stage of emerging adulthood (18-26 years old). Sleep abnormality may have an effect through impacting physical and mental wellbeing (13)(14)(15)(16), along with fluctuations of several hormones such as cortisol, leptin, melanocortin (1,(17)(18)(19). In addition, problematic smartphone use (PSU) and psychological distress such as depression may also affect both sleep quality and EDs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring associations between dietary patterns and lifestyle variables are sparse. Previous reports showed associations between unhealthy lifestyles, such as current smokers [31], sedentary behavior [32], or poor sleep [33], with unhealthy diets. Furthermore, a nationally representative study in Mexico showed that the "re ned foods and sweets" pattern had the highest alcohol contribution [4].…”
Section: Discussionmentioning
confidence: 98%